Praktik Jual Beli Getah Karet - Maiyati Ritonga; Zulfan Efendi Hasibuan; Sawaluddin Siregar (IAIN Padangsidimpuan, 2022)
Buying and selling is exchanging maal (goods or property) with maal which is carried out in acertain way. Or exchange goods of value with the like in a legal way. In buying and selling, the seller must be honest, based on the desire that for others to get the goodness and happiness he wants.In the problem of buying and selling in tanjung marulak, where some rubber farmers sell rubber latex which is amixture of sand, wood, leaves into the rubber sap and this can damage the quality of the rubber sap.The main point of the problem in this study, the author is interested in triying to examine more deeply about how the practice of buying and selling rubber sap in Tanjung Marulak hamlet, Huta Godang Village, Kec. Sungai Kanan Kab.Labuhan Batu Selatan and how to review the compilation of syariah economic law on the sale and purchase of rubber latex in the hamlet of Tanjung Marulak.This study uses the field research method (field research) and is sourced from primary and secondary data. The data collection techniques used in this study were observation.And the results of the research that the practice of buying and selling rubber sap in tanjung marulak hamlet, huta godang village, kec sungai kanan kab. Labuhan batu selatan in the sale and purchase thereis a fraud comittied by the seller, this fraud has become a habit for some of the farmers, they mix rubber sap with sand, wood, leaves so that there are parties who feel disadvantaged, namely Tokesap, because mixing rubber sap can damage its quality and if sold the factory the price is cheaper and sometimes Toke dosen’t sell sap wich has a mixture of sand, wood,leaves. The sale and purchase of the latex when viewed from the perspective of the compilation of sharia economic law, the terms and conditions are valid, and in article 76 it has been explained in the section that “the goods being traded must be known by the buyer” but in the object of the sale and purchase there are parties who don’t know the object, this can be resulting in the loss of one of the parties, in buying and selling the perpetrator must know the principle of like and equal. Love the freedom of transactions.